GENDER INEQUALITY IN MALLADI’S THE NEAREST EXIT MAY BE BEHIND YOU - Manonmani, J.Rebecca; Jebaruby, Y.Vigila (International Journal of Psychosocial Rehabilitation, 2025)
Gender inequality is the lack of equality in the attitudes of people which is established based on the gender of the people. It tends to reflect and mean so much in so many aspects of people’s lives. Gender inequality and the resulting discrimination on the basis of sex are widely observed and acknowledged all over the world. Despite government steps to fight gender discrimination, gender inequalities persist within the family and at work place. The patriarchal system and its values are at the root cause of the majority of forms of discrimination against women. In their own families, women are dominated by their male relatives. Women have little decision-making power in the patriarchal dominated societies. The purpose of this paper is to investigate the nature and extent of gender inequality in Asmi's family and in her workplace. The study's main goals are to examine women's power dimensions in the family and workplace, as well as their participation in decision-making process. This empirical study is based on the life of Asmi, an Indo-American woman, who immigrates to the United States to get better job opportunities in America after completing her graduation but she gets American citizenship. The majority of women believe that if more women get more jobs gender inequality will be eradicated. However, this novel reveals that gender inequality exists in the family and in the workplace, even though many women get work in the work places.Factors determining these inequalities include a woman's employment status, her age, her marital status and the number of children she has. Malladi also suggests the ways to achieve gender equality and how the protagonist rises to the position of Vice President of her company despite constant discrimination and harassment against her.